Usability Evaluation of MySAPK BKN using The System Usability Scale (SUS) Method : Case Study Human Resources Development and Personnel Agency Banggai Regency - Elin Cahyaningsih; Haryati Asgap Jelang (Diponegoro University, 2025)
The administration of state apparatus services requires an integrated and reliable information system to ensure the availability of accurate and up-to-date personnel data. MySAPK BKN is the mobile application prepared to support the availability of personnel data. Using MySAPK BKN is part of Digital Transformation and a Roadmap for Bureaucratic Reform towards Good Governance. The use of MySAPK BKN requires continuous evaluation to be able to meet user needs. Thus, it is necessary to continue to develop and evaluate its implementation, especially in the scope of usability. This evaluation can be applied by using the System Usability Scale (SUS) method. The use of the SUS method was carried out to determine the usability level of MySAPK BKN at the Personnel and Human Resources Development Agency in Banggai Regency. The research method is quantitative research. Data was obtained through the SUS questionnaire using Likert scale questions and collected from April 2023 to May 2023. This questionnaire is addressed to 47 employees who have used MySAPK BKN. The results show that the implementation of MySAPK BKN using the SUS method was the Good category with an average SUS score of 70. This score indicates that users are satisfied with the use of this application. This research recommends continuing to evaluate the use of the application and ongoing socialization and training the use of MySAPK BKN. Even though a score of 70 is included in the good category, it is just the Standard category in application use.